Anti corruption disclosure by CSR best practices companies: a case of Malaysia and Indonesia/ Corina Joseph… [et.al.] - Joseph, Corina; Sawani, Yussri; Rahmat, Mariam; Noyem, Josephine Avelind; Ajom, Westmoreland; Gunawan, Juniati (2014)
Corruption occurs in various settings all over the world. Previous studies on CSR in Malaysia have focussed on the examination of disclosure in annual reports. This proposed study takes a different step by ascertaining whether corruption prevention strategies are included in the CSR practices of selected Malaysian profit and non- profit organizations The objectives of the study are: 1) To explore the inclusion of corruption prevention strategies into CSR practices; 2) To identify factors that influence / impede the inclusion of corruption prevention strategies into CSR practices. Data collection involves 2 phases. The first phase covers the content analysis of annual reports / CSR stand alone reports for 43 ACCA MaSRA award 2011 entrants In the second phase, data will be collected through focus group interviews conducted with personnel involved in CSR practices implementation in selected Malaysian profit and non-profit organizations.